Positive allosteric interactions on cardiac muscarinic receptors: effects of chemical modifications of disulphide and carboxyl groups - Jakubík, J; Tucek, S (European journal of pharmacology, 1995)
Changes in the allosteric effects of alcuronium on rat cardiac muscarinic receptors were investigated after chemical modifications of S-S bonds or free carboxyl groups. In membranes pretreated with dithiothreitol, alcuronium lost its positive action on the binding of [3H]methyl-N-scopolamine while its inhibitory effect on radioligand dissociation was preserved. In membranes pretreated with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), known to modify free carboxyl groups in proteins, the ability to bind [3H]methyl-N-scopolamine was preserved if the pretreatment had been performed in the presence of alcuronium, methyl-N-scopolamine or carbachol, while the positive cooperative effect of alcuronium on [3H]methyl-N-scopolamine binding was only preserved in membranes that had been exposed to EDC in the presence of alcuronium. Methyl-N-scopolamine, carbachol and alcuronium differed in their ability to protect (against EDC) the action of alcuronium on the rate of [3H]methyl-N-scopolamine dissociation. The results suggest that the disulphide bridge connecting the first two extracellular loops of muscarinic receptors is important for the positive allosteric action of alcuronium and that three carboxyl groups (presumably aspartate residues) are involved in receptor interactions with alcuronium and methyl-N-scopolamine. The first group is important for the effect of alcuronium on the affinity for methyl-N-scopolamine, the second is critical for the effect of alcuronium on the rate of methyl-N-scopolamine dissociation, and the third is critical for methyl-N-scopolamine binding. Presumably, the two charged nitrogens of alcuronium associate with the first and the second of the three groups involved.
Keywords: Dose-Response Relationship, Drug; Female; krysa rodu Rattus; alosterické místo; radioligandová zkouška; Alcuronium; receptory muskarinové; zvířata; skopolamin; Dithiothreitol; potkani Wistar; časové faktory; alkuronium; ženské pohlaví; Rats, Wistar; Male; Allosteric Site; Heart; Radioligand Assay; Rats; Receptors, Muscarinic; vztah mezi dávkou a účinkem léčiva; Animals; mužské pohlaví; dithiothreitol; Time Factors; Scopolamine; srdce